2016
DOI: 10.1536/ihj.16-149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allopurinol on Myocardial Energy Metabolism in Chronic Heart Failure Rats After Myocardial Infarct

Abstract: SummaryTo determine the effect of the xanthine oxidase (XO) inhibitor allopurinol on myocardial energy metabolism in a chronic heart failure rat model after myocardial infarct.An AMI model was established in 6-week-old rats via the ligation of the anterior descending coronary artery. Thirty-five rats were randomly divided into the following 3 groups: an ALLO group, an AMI group, and a Sham group. Heart failure was successfully diagnosed via echocardiography and blood tests. Xanthine oxidase (XO), malondialdehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…These unfavorable effects may have resulted in impaired systolic function. Because previous studies have shown some agents have favorable effects on myocardial energy metabolism, 24,25) there might be some interventions that improve the energy efficiency of CD36-deficient heart under pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…These unfavorable effects may have resulted in impaired systolic function. Because previous studies have shown some agents have favorable effects on myocardial energy metabolism, 24,25) there might be some interventions that improve the energy efficiency of CD36-deficient heart under pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the pharmacological inhibition of Xantine Oxidase, by allopurinol. First, in both rat and mouse models of dilated cardiomyopathy, administration of allopurinol is able to decrease the level of ROS, which contributes to slow down the disease (Engberding et al, 2004 ; Wang Z. et al, 2016 ). Interestingly, in a clinical study led on HF patients, allopurinol was able to restore M-CK activity, hence to sustain the transfer of energy from mitochondria to sarcomere (Hirsch et al, 2012 ).…”
Section: Discussion: Therapeutic Strategiesmentioning
confidence: 99%
“…By affecting both mitochondrial proteins and phospholipids, ROS also exacerbate the disruption of the mitochondrial respiratory chain and the loss of ATP production. Additional studies described that increase of ROS production by xanthine oxidase is involved in impaired energy metabolism during heart failure and myocardial infarction, and allopurinol (inhibitor of xanthine oxidase) prevents these deleterious effects (Wang Z. et al, 2016 ; Schuchardt et al, 2017 ).…”
Section: Oxygen Consumption and The Double-edged Redox Signaling In Cmentioning
confidence: 99%
“…Ultrathin sections of the infarct, border, and remote regions were prepared using a Leica EM UC7 ultramicrotome (90-120 nm thick) and stained with uranyl acetate and lead citrate on a grid for TEM (H-7650; Hitachi, Tokyo, Japan). 17) Statistical analysis: JMP software (JMP 12; SAS Institute, Inc., Cary, NC, USA) was used for statistical analysis. Continuous values are presented as the mean ± standard deviation.…”
Section: Definition Of Myocardial Areasmentioning
confidence: 99%